2017
DOI: 10.1093/toxsci/kfx028
|View full text |Cite
|
Sign up to set email alerts
|

Early-Life Benzo[a]Pyrene Exposure Causes Neurodegenerative Syndromes in Adult Zebrafish (Danio rerio) and the Mechanism Involved

Abstract: There is increasing recognition of the importance of early-life environmental exposures in health disorders at later-life stages. The aim of this study was to evaluate whether early-life exposure to benzo[a]pyrene (BaP) could induce neurodegenerative syndromes at later-life stages in zebrafish. Embryos were exposed to BaP at doses of 0, 0.05, 0.5, 5, and 50 nM from early embryogenesis to 96 h post-fertilization (hpf), then transferred to clean water and maintained for 365 days. We found that BaP decreased loco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 58 publications
2
12
0
Order By: Relevance
“…In the current study, SE mediated the impact of prenatal PAH exposure on behavioral problems. The finding that higher prenatal exposure to PAH predicted lower SE was consistent with the animal models showing the inverse relation between prenatal PAH exposure and locomotor activity (Gao et al., 2017; Suzuki et al., 2010). Other air pollutants, such as PM 2.5 and traffic‐related air pollution, have also been linked to decreased locomotion, partly due to a decrease in hippocampal brain‐derived neurotrophic factor (BDNF) expression (Zhou et al., 2020) and reduced striatal dopamine (Yokota et al., 2009), respectively.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In the current study, SE mediated the impact of prenatal PAH exposure on behavioral problems. The finding that higher prenatal exposure to PAH predicted lower SE was consistent with the animal models showing the inverse relation between prenatal PAH exposure and locomotor activity (Gao et al., 2017; Suzuki et al., 2010). Other air pollutants, such as PM 2.5 and traffic‐related air pollution, have also been linked to decreased locomotion, partly due to a decrease in hippocampal brain‐derived neurotrophic factor (BDNF) expression (Zhou et al., 2020) and reduced striatal dopamine (Yokota et al., 2009), respectively.…”
Section: Discussionsupporting
confidence: 84%
“…Previous animal studies showed a decrease in dopamine and serotonin in zebrafish due to PAH exposure (Gao et al, 2017;Vignet et al, 2017). Exposure-related reductions in dopamine and serotonin might lead to increased fear (Clinton, Stead, Miller, Watson, & Akil, 2011;Gao et al, 2017) and increased frustration (de Almeida, Ferrari, Parmigiani, & Miczek, 2005). Prenatal exposures to other air pollutants (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This was unexpected and may have been due to a mechanism different from AHR2/ARNT acting via AHREs in the dnmt promoters. Another study found that, following BaP exposure, dnmt1 and dnmt3a had increased mRNA expression in 96-hpf larvae and in adult brains; however, the role of the AHRs in mediating the altered expression was not investigated (Gao et al, 2017).…”
Section: Epigenetics and Multigenerational Effectsmentioning
confidence: 99%
“…Due to its chemical and thermal stability as well as due to its bioaccumulation and dissolution properties, benzpyrene has mutagenic, embryotoxic, and haematotoxic impact on living beings, as it is stated at nekurim.ru. According to Gao D. et al (2017) and Rozanova E. et al (2009), benzpyrene is extremely harmful to human health. Their findings are supported by Gupta P.D.…”
Section: Figure 1: Growth Dynamics Of Pollutants Emission By Vehiclesmentioning
confidence: 99%